Comparative extraction strategies for Adhatoda vasica: Unveiling bioactive profile via GC–MS and their scavenging potential - Abdul Jabbar; Shahid Iqbal; Umer Younas; Arfaa Sajid; Qaisar Manzoor; Zohaib Saeed; Anam Sajid; Awais Ahmad; Dongwhi Choi (Results in Chemistry)
Adhatoda vasica (L.) Nees holds prominence as a medicinal plant in Unani and Ayurvedic traditions. This study evaluates conventional versus modern extraction processes for isolating bioactive constituents from Adhatoda vasica leaves (AVL), using soxhlet extraction (SE), cold maceration (CM), microwave assisted extraction (MAE), and ultrasound assisted extraction (UAE) techniques and evaluate their scavenging potential. The maximum extraction yield (34.56 %) was achieved using MAE, followed by UAE, SE, and CM. The radical scavenging potential of AVL bioactive compounds was evaluated using 2,2-Diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), iron chelating (ICS), and 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assays. Results indicated that DPPH and ABTS showed 38.45 ± 1.87 % and 76.19 ± 0.98 % inhibition, respectively. The reducing power capacity was observed as 461.56 ± 1.90 mmol AAE/10 g, while iron chelating activity was 65.3 ± 1.76 μg Na₂EDTA/10 g. The MAE fraction exhibited the highest contents of flavonoids (46.21 ± 1.96 μg ECE/g), phenolics (55.69 ± 1.54 mg GAE/g), tannins (5.77 ± 1.57 mg TAE/g), and ascorbic acid (36.4 ± 1.54 mg AA/100 g). Due to highest scavenging potential chemical profiling of MAE fraction was performed using gas chromatography–mass spectrometry (GC–MS) and high-performance liquid chromatography (HPLC). GC–MS analysis without derivatization identified fourteen compounds, while derivatization with N,O-bis(trimethylsilyl) trifluoro acetamide revealed twelve additional compounds; n-butanol and ethanol fractions exhibited two and four compounds, respectively. HPLC analysis confirmed the presence of major phytochemicals including quercetin, gallic acid, syringic acid, and vitamin C. The results exhibit that AVL are abundant with phenolic compounds, and microwave-assisted extraction are highly effective in maximizing the yield of bioactive components. Due to their potent radical scavenging properties, these bioactives hold significant potential for use in the food, pharmaceutical, and cosmetic industries.